Fine tuning the composition and nanostructure of Fe-based core-shell nanocatalyst for efficient CO2 hydrogenation - Gupta, Sharad; Jain, Vivek K.; Jagadeesan, Dinesh (Chemnanomat, 2016)
Hydrogenation of CO2 to hydrocarbons is one of the crucial technologies to address the energy deficit and increasing environmental pollution. In this work, we have synthesized and systematically studied the influence of composition and nanostructure of a Fe-based, carbon-coated core shell nanocatalyst. The synthesis method offered good control over the thickness of the carbon coating in the core shell catalyst, which in turn controlled the chemical composition of the core. The results emphasized an optimal amount of Fe3O4, Fe5C2 in the core and partially graphitized carbon in the shell for a high catalytic activity in the conversion of CO2 at atmospheric pressure with higher selectivity to C-2-C-4 olefins.

Engineering pore morphology using silica template route over mesoporous cobalt oxide and its implications in atmospheric pressure carbon dioxide hydrogenation to olefins - Gupta, Sharad; Ciotonea, Carmen; Royer, Sebastien; Dacquin, Jean-Philippe; Vinod, C. P. (2020)
Highly ordered mesoporous cobalt oxides (denoted as m-Co-KIT-6 and m-Co-SBA-15) with three dimensional and two dimensional pore morphology respectively have been synthesized using 3D KIT-6, and 2D SBA-15 as silica template via nanocasting route. CO2 hydrogenation activity was evaluated for these mesoporous materials under atmospheric pressure conditions. In comparison to nanoparticles of cobalt oxide (Co3O4-nano), mesoporous catalysts showed excellent activity for CO2 hydrogenation due to their higher number of exposed active sites and lower mass diffusion limitations. The ordered mesoporous structure of Co3O4 catalysts favored the chain growth of carbon atoms for the production of C2+ hydrocarbons while Co3O4 nanoparticles showed strong selectivity toward CH4. High selectivity for C2+ (similar to 25%) was obtained for both m-Co-KIT-6 and m-Co-SBA-15 catalysts at 320 degrees C. In addition, the 3D pore structure of m-Co-KIT-6 catalyst exclusively formed more olefins (54.9%) fraction. (C) 2020 Published by Elsevier Ltd.
Keywords: CO2 hydrogenation; Mesoporous CO3O4; Olefin fraction; Pore morphology; Silica hard template

Role of exposed crystal facets in the atmospheric pressure CO hydrogenation on Co3O4 - Jain, Preeti; Gupta, Sharad; Vinod, C. P. (Nano-Structures & Nano-Objects, 2020)
Co3O4 nanostructures with different exposed planes are studied for atmospheric pressure CO hydrogenation. Existence of different facets is characterized by HR-TEM and found Co3O4 - NSP (nanospheres) expose (112) facet, NB (nanobelts) exhibit (110) plane and (100) is the dominant surface facet in NC (nanocubes). Different catalytic activity is demonstrated by the specific facet of Co3O4 catalysts. CO hydrogenation is facet dependent and the catalytic activity follows the order of Co3O4-NB > Co3O4-NC > Co3O4-NSP.

Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates

Morphology-dependent catalysis by Co3O4 nanostructures in atmospheric pressure carbon dioxide hydrogenation - Gupta, Sharad; Jain, Preeti; Jagadeesan, Dinesh; Vinod, C. P. (Journal of Physical Chemistry C, 2023)
In this work, three Co3O4 nanostructureswith different morphologies (cubes, rods, and sheets) were synthesizedusing a hydrothermal method and tested for the CO2 hydrogenationreaction. The physicochemical properties of the structured Co3O4 were well characterized by X-ray diffraction(XRD), Raman spectroscopy, field-emission scanning electron microscopy(FESEM), transmission electron microscopy (TEM), high-resolution transmissionelectron microscopy (HRTEM), hydrogen temperature-programmed reduction(H-2-TPR), and X-ray photoelectron spectroscopy (XPS) techniques.Based on the characterization, cube, rod, and sheet Co3O4 nanostructures were found to expose the (100), (110),and (112) planes, respectively. The effect of cobalt oxide morphologieswith different exposed surfaces on the activity and selectivity towardCO(2) hydrogenation reaction in a plug-flow reactor operatedbetween 200 and 400 & DEG;C under atmospheric pressure conditionswas explored. The results establish a correlation of the catalyticactivity with morphological structures in the order rods > sheets> cubes. H-2-TPR and XPS studies demonstrated that thehighreducibility of Co3O4 rod makes it an excellentcatalyst for CO2 hydrogenation.

Atmospheric-pressure continuous-flow methane oxidation to methanol and acetic acid using H2O2 over the Au-Fe catalyst - Jagtap, Anuradha V.; Kumar, Pawan; Gupta, Sharad; Nagendra, Abharana; Jha, Shambhu Nath; Bhattacharyya, D.; Ajithkumar, Thalasseril G.; Vinod, C. P. (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: CO oxidation; HIGHLY SELECTIVE OXIDATION; metal-organic frameworks

Exploring the CeO2 support morphology for the carbon dioxide hydrogenation reaction using nickel catalysts - Gupta, Sharad; Jagtap, Anuradha; Vinod, C. P. (Journal of Physical Chemistry C, 2024)
The catalytic activity and stability are examined for the hydrogenation of carbon dioxide under atmospheric pressure over 2 wt % Ni/CeO2 nanorods (2Ni-CeNRs), nanocubes (2Ni-CeNCs), and nanopolyhedra (2Ni-CeNPs). The 2Ni-CeNR catalysts display excellent catalytic activity and higher stability compared with 2Ni-CeNC and 2Ni-CeNP catalysts. A comprehensive understanding of the surface atomic and electronic structure versus activity has been derived using high-resolution electron microscopy and spectroscopy techniques. High metal dispersion, strong metal-support interaction (SMSI) effect and abundant oxygen vacancies are deduced to play a crucial role in determining the catalytic activity and selectivity of the CO2 hydrogenation reaction.

Exploring the electronic modulation in controlling the activity and selectivity of Ni-Au-In based catalyst in atmospheric pressure CO2 hydrogenation - Bajpai, Jyotsna P.; Gupta, Sharad; Goud, Devender; Deka, Diku Raj; V. Jagtap, Anuradha; Kumar, Pawan; Ahamed, Momin; Peter, Sebastian C.; Vinod, C. P. (Chemical Engineering Journal, 2025)
Nickel-based catalysts are widely used for the hydrogenation of CO2 but encounter stability challenges during prolonged reactions and at elevated temperatures. At atmospheric pressure, nickel primarily promotes methane formation in CO2 hydrogenation reactions. In this work, we demonstrate that the stability and activity of nickel can be significantly enhanced through gold (Au) modification. Furthermore, we achieve a near-complete selectivity switch from methane to CO by incorporating indium (In), mediated through the formation of Au-In alloy. This catalyst exhibits excellent CO2 conversion and CO selectivity at relatively lower temperatures (400 degrees C), addressing a major bottleneck in the Reverse Water-Gas Shifts (RWGS) reaction. XPS studies demonstrate an interesting electron transfer mechanism facilitated by gold, which involves the formation of electronrich Au species (Au delta-) and the development of Au-In alloys. This process improves the reducibility of nickel oxide while allowing a fraction of nickel to remain in its metallic form, managing a facile hydrogenation process and regulating the shift in selectivity from CH4 to CO.
Keywords: Alloy formation; Bimetallic catalyst; CO2 hydrogenation; RWGS; Selectivity switch; synergy; Trimetallic catalyst; XPS (X-ray photoelectron spectroscopy)

Hydrogenation of CO2 catalyzed by thermally decomposed cobalt-containing alkaline earth metal carbonates - Gupta, Sharad; Vinod, C. P.; Poupin, Christophe; Jagadeesan, Dinesh (Energy & Fuels, 2025)
CO2 hydrogenation over Co catalysts supported on alkaline earth metal oxides was investigated. The catalysts were prepared by thermally decomposing alkaline metal carbonates CoMCO3, where M = Mg, Ca, Sr, and Ba, in H2. During the thermal activation, contingent upon the thermal stability of the precursor, it transformed into a composite of metal oxides, metals, and undecomposed metal carbonates. The thermal activation temperature, the ratio of CO2 to H2, the composition, and the basicity of the catalyst all played a significant role in influencing the conversion of CO2 and the selectivity to CH4. Among the various Co-containing alkaline earth metal carbonate precursors, CoCaCO3 activated at 400 degrees C yielded the highest steady-state CO2 conversion of 54% with a CH4 selectivity of 89.8% throughout 28 h in the reaction stream containing a 1:4 ratio of CO2 and H2. Detailed characterization showed that the CaCo-400 catalyst contained metallic Co, CaO, and undecomposed CaCO3 phases. The study assumes significance in understanding the role of the composition of catalysts in the formation of CO2 hydrogenation.

Unravelling the Cu-Co nanoparticle synergy over Ceria-Zirconia support toward efficient reverse water gas shift (RWGS) conversion under H2 lean conditions - Jagtap, Anuradha Vijay; Bamnia, Mahesh Kumar; Maibam, Ashakiran; Bajpai, Jyotsna Paliwal; Gupta, Sharad; Thomas, Sharon K.; Dabke, Niteen B.; Vinod, C. P. (Chemical Engineering Journal, 2025)
CO2 emissions leading to global warming and environmental and socio-economic issues have propelled the research community to develop technologies capable of capturing and converting CO2 into valuable products. Controlling the selectivity toward platform molecules like CO, methanol, or methane is a fundamental challenge in CO2 hydrogenation. Supported cobalt nanoparticles are known for hydrocarbon production through FischerTropsch (FT) reaction, and Cu-based catalysts are known for reverse water gas shift (RWGS) reaction. Here, we show that d-band centre can be carefully modulated by making bimetallic combinations of Cu and Co for a highly active RWGS catalyst. An oxygen vacancy-rich nanostructured ceria-zirconia (CZ) support with Cu nanoparticles (2 wt%) modified with as low as 0.05 wt% Co shows excellent conversion for CO2 hydrogenation and selectivity for CO below 500 degrees C. The optimized catalyst shows CO2 conversion even under hydrogen lean conditions (H2/ CO2 ratio 0.5:1), with a breakthrough rate of 206023 mmol/gmetal/h for CO at 600 degrees C, having H2 utilization of 80% for the RWGS process.
Keywords: Bimetallic catalyst; Ceria-zirconia; CO 2 hydrogenation; Cobalt catalyst; Copper catalyst; Reverse water gas shift (RWGS); synergistic effect